Biogeochemical cycles and climate - Dolman, A. J. (Oxford University Press, 2019)
This book describes the interaction of greenhouse gasses with the Earth System. It takes the perspective of the Earth as an integrated system and provides examples of both changes in our current climate and those in the geological past. The book gives a required elementary description of the physics of the earth system, the atmosphere and ocean.
Keywords: Biogeochemical cycles.; Climatic changes.; Environmental geochemistry.; elektronické knihy; electronic books